Modified Delphi in adapting a tool to assess the level of knowledge and practice on adult enteral nutrition therapy among nurses - Piyumi L Weerawardhana; Lalitha Meegoda MKD; Sampatha E Goonewardena (Asian Journal of Medical Sciences, 2022)
Background: Enteral nutrition (EN) is the preferred method of nutritional administration for critically ill patients according to the world’s standards. Nurses have a key role in delivering EN and assessing nurses’ knowledge and practice on this, are crucial for maintaining quality nursing care.